PANDANGAN TAMĀM HASSĀN TENTANG ‘ĀMIL DALAM ILMU NAHWU - Abdul Basith (Sunan Kalijaga State Islamic University Yogyakarta, 2008)
In Arabic Linguistics, Nahwu or Arabic Syntax has established for centuries. However, its complexities make the modern Arabic linguists re-formulate it so that it can be comprehended better by the native and speakers of Arabic as a second language. One of those linguists is Tamâm Hassân, who put Arabic language in a more (al-manhaj alwashfi) established position by perfecting its phonology, morphology, syntax, and semantic. His view over ‘âmil as a central theme and pillar in Arabic syntax or Nahwu reformulates the Arabic syntax by using descriptive approach (al-manhaj al-washfi). This makes Nahwu become more comprehensible.